2002
DOI: 10.1021/pr0155127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc and Temperature on the Conformation of the γ Subunit of Retinal Phosphodiesterase:  A Natively Unfolded Protein

Abstract: The cyclic GMP phosphodiesterase gamma-subunit (PDEgamma) was shown to belong to the family of natively unfolded proteins. Increasing temperature transforms the protein into a more ordered (but still relatively disordered) conformation. The C-terminal part of PDEgamma has a high-affinity zinc-binding site (Kd approximately 1 microM), with His75 and His79 being directly involved into the coordination of Zn2+. Zinc-loaded protein remains effectively unfolded. Possible implications of these findings to the functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
54
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 67 publications
4
54
0
1
Order By: Relevance
“…Amino acid analysis and biochemical studies of PDE␥ had led to the conclusion that PDE␥ is an IDP (7,8). We found that the peaks in the 2D [ 1 H-15 N]-HSQC NMR spectrum of PDE␥ exhibited narrow linewidths with poorly dispersed amide proton chemical shifts [see supporting information (SI) Fig.…”
Section: Pde␥ Is Intrinsically Disordered But Exhibits Transient Secomentioning
confidence: 99%
See 2 more Smart Citations
“…Amino acid analysis and biochemical studies of PDE␥ had led to the conclusion that PDE␥ is an IDP (7,8). We found that the peaks in the 2D [ 1 H-15 N]-HSQC NMR spectrum of PDE␥ exhibited narrow linewidths with poorly dispersed amide proton chemical shifts [see supporting information (SI) Fig.…”
Section: Pde␥ Is Intrinsically Disordered But Exhibits Transient Secomentioning
confidence: 99%
“…Residue V66 of PDE␥ interacts with RGS9, which further tightens the association between ␣ t and RGS9. The C-terminal region of PDE␥ also interacts with the catalytic domain of PDE6; however, studies have suggested that this interaction involves the 11 C-terminal residues of PDE␥, a region distinct from the ␣ t interaction site (6).It has been demonstrated that PDE␥ belongs to the growing family of intrinsically disordered proteins (IDPs) (7,8). Presumably, the inherent structural plasticity of an IDP, such as PDE␥, confers an advantage in its ability to interact with multiple partners (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…What has not been elucidated is whether this increased level of folding is critical for nanosphere formation and whether it is a consequence of assembly or a consequence of other parameters, such as temperature and pH. Several studies have previously shown that IDPs can undergo significant conformational alteration upon dimerization and subsequent oligomerization (18,19).…”
mentioning
confidence: 99%
“…The C-terminal region (broadly defined as amino acids 62-87) interacts with the catalytic domain and blocks the catalytic activity (8,9,(13)(14)(15)(16)(17). Structural studies of P␥ in solution indicate that this protein is overall an intrinsically disordered protein (18) but contains ␣-helical secondary structure (␣1, ␣2, and ␣3; Fig. 1A) in its C-terminal region (19); the ␣-helical content within the C-terminal region of P␥ is also observed when this region of P␥ forms a complex with either transducin (20) or a chimeric PDE5/6 catalytic domain (21).…”
mentioning
confidence: 99%